A case of erythema multiforme drug eruption associated with erythrodermic psoriasis induced by sofosbuvir and daclatasvir. (18th October 2016) - Wang, Y.; Liu, P.
Summary: What is known and the objective: Sofosbuvir (SOF) and daclatasvir (DCV) have revolutionized the treatment of hepatitis C virus and now represent the preferred therapy for this disease. Limited data are available on the dermatological side effects resulting from co‐administration of SOF and DCV. Case description: We report a case of an erythema multiforme drug eruption associated with erythrodermic psoriasis induced by SOF and DCV. After ceasing treatment, the skin condition significantly improved. What is new and conclusion: We should pay attention to adverse skin reactions resulting from SOF and DCV, especially if the patient has a pre‐existing dermatosis. Abstract : A CHC patient was treated with SOF and DCV. After 23 days' treatment, he appeared erythema multiforme drug eruption associated with erythrodermic psoriasis. After treatment, his skin condition significantly improved. We should pay attention to adverse skin reactions resulting from SOF and DCV, especially if the patient has dermatosis.